Automatic Portal Design Using Ultra High Frequency - RFID - Fashiha Ilman, Abdillah; Jauhari, Moh.; Sohibul Hajah, M.; Nur, Mohammad; Basya Shahrys Tsany, Rahmat; Dzulkiflih, Dzulkiflih (Universitas Muhammadiyah Surakarta, 2026)
The development of science and technology has experienced a very high acceleration. Along with this, the need for and demand for fast and accurate information is also getting higher. Based on this, this research aims to create an automatic portal model using UHF RFID. In addition, this model will have digital data documenting entry and exit of vehicles, so that it is easier in the process of monitoring data on students, lecturers and guests in carrying out activities within the Madura State Polytechnic (POLTERA) campus. To help security officers, and prevent transmission of Covid-19, an automatic entry and exit control system is needed. The purpose of this research is to design and build an automatic portal with RFID that has Ultra High Frequency (UHF) technology and additional driver body temperature detection technology. The temperature value and the RFID code are read by the RFID Reader and then the code is used as a condition for access to open and close the portal. After that, the recorded data in the form of RFID card data, temperature data, and driver images will be stored in a microSD data logger.